Community-Based Learning Laboratories as Alternative Pathways to Sustainable Education and Empowerment: Insights from Indonesia - Qowim, Muhammad; Libriyanti, Yuyun (Proceeding International Conference on Religion, Science and Education, 2026)
Mainstream formal schooling often fails to address the diverse needs of marginalized communities. In Indonesia, community-based laboratories, specifically Sanggar (art studios), Dojo (martial arts centers), and Pesantren (Islamic boarding schools), have emerged as innovative educational ecosystems. This study explores how these laboratories function as alternative pathways for education and empowerment aligned with the Sustainable Development Goals (SDGs). Using an exploratory-descriptive qualitative design, data were collected through participatory fieldwork, including interviews and focus group discussions at three laboratories in Yogyakarta affiliated with UIN Sunan Kalijaga. The findings reveal that these laboratories serve as “educational safety nets” for school dropouts (SDG 4), create livelihood pathways through professional certification and art business ecosystems (SDG 8), and foster “living heritage” through intergenerational knowledge transfer (SDG 11). The study concludes that recognizing and integrating these non-formal models into the national education agenda is crucial for building a more inclusive and resilient learning society.